Plasma and Magnetic Field Turbulence in the Earth’s Magnetosheath at Ion Scales - Rakhmanova, Liudmila; Riazantseva, Maria; Zastenker, Georgy (Frontiers in Astronomy and Space Sciences, 2021)
Crossing the Earth’s bow shock is known to crucially affect solar wind plasma including changes in turbulent cascade. The present review summarizes results of more than 15 years of experimental exploration into magnetosheath turbulence. Great contributions to understanding turbulence development inside the magnetosheath was made by means of recent multi-spacecraft missions. We introduce the main results provided by them together with first observations of the turbulent cascade based on direct plasma measurements by the Spektr-R spacecraft in the magnetosheath. Recent results on solar wind effects on turbulence in the magnetosheath are also discussed.